A case series of laryngeal papilloma management in children - Reddy, Anil Jangam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Squamous papillomata caused by the human papillomavirus (HPV) are the most common benign neoplasms seen by laryngologists. I hereby presenting a case series of laryngeal papilloma in pediatric age with varied outcome following surgery. Microlaryngoscopy guided excision using cold steel instruments and cautery (if required) was the treatment of choice in our cases. Of the 2 cases one did not recur but the other 2 had recurrence who underwent second surgery with oral antivirals post operatively. Papilloma treatment should be individualized/ tailor made because recurrence rate varies.